Dynamic weight status changes and peer lifestyles in early adolescence: A social network analysis on a longitudinal cohort of Taiwanese youth. Issue 6 (November 2022) - Lee, Chih-Ting; Chen, Tsai-Wei; Ubeda Herrera, Josue Jaru; Yu, Yi-Fang; Strong, Carol; Lin, Chung-Ying; Chang, Yun-Hsuan; Hsieh, Yi-Ping; Lin, Yi-Ching; Tsai, Meng-Che
Abstract: Background: Friendship networks are relevant to adolescent weight status and lifestyle, but little is known about their relationship in an East Asian setting. Using a longitudinal cohort of Taiwanese adolescents, we studied how weight status and lifestyles might influence friendship. Simultaneously considering the influence of friendship networks, we further examined the effects of peers' lifestyles on the body weight status of adolescents. Methods: Data were retrieved from the first three waves of the Taiwan Youth Project (N = 2409; 51 % boys). Participants were asked to nominate their friends at school and to report their lifestyle factors (e.g. sleep habits, internet use, and athletic performance). Weight status was proxied by body mass index calculated from self-reported weight and height. Stochastic actor-based modeling was used for the friendship network analyses. Results: Considering network structure, adolescents selected friends based on similarities in weight status (β = 0.147 [standard error = 0.044], p < 0.001) and lifestyle factors, such as athletic performance (β = 0.181 [0.034], p < 0.001), internet use (β = 0.156 [0.039], p < 0.001), and social jetlag (β = 0.055 [ ± 0.022], p < 0.05). In the behavior dynamics model, we did not observe any peer influence on changes in adolescents' weight status. Conclusion: These findings suggest a pervasive homophilic friendship selection explained by weight and lifestyle-based similarities, despite no evidence of peer influence on weight status. Stakeholders and care providers of adolescent health should be aware of the social network processes that underlie weight problems.